Five Cu(I) and Zn(II) clusters and coordination polymers of 2-pyridyl-1,2,3-triazoles: Synthesis, structures and luminescence properties - Bai Shi-Qiang (Royal Society of Chemistry, 2016)
10.1039/c4ce02282c